Impact of Language Experience on Attention to Faces in Infancy: Evidence From Unimodal and Bimodal Bilingual Infants - Mercure, Evelyne; Quiroz, Isabel; Goldberg, Laura; Bowden-Howl, Harriet; Coulson, Kimberley; Gliga, Teodora; Filippi, Roberto; Bright, Peter; Johnson, Mark H.; MacSweeney, Mairéad (Frontiers in Psychology, 2018)
Faces capture and maintain infants’ attention more than other visual stimuli. The present study addresses the impact of early language experience on attention to faces in infancy. It was hypothesized that infants learning two spoken languages (unimodal bilinguals) and hearing infants of Deaf mothers learning British Sign Language and spoken English (bimodal bilinguals) would show enhanced attention to faces compared to monolinguals. The comparison between unimodal and bimodal bilinguals allowed differentiation of the effects of learning two languages, from the effects of increased visual communication in hearing infants of Deaf mothers. Data is presented for two independent samples of infants: Sample 1 included 49 infants between 7 and 10 months (26 monolinguals and 23 unimodal bilinguals), and Sample 2 included 87 infants between 4 and 8 months (32 monolinguals, 25 unimodal bilinguals, and 30 bimodal bilingual infants with a Deaf mother). Eye-tracking was used to analyze infants’ visual scanning of complex arrays including a face and 4 other stimulus categories. Infants from 4 to 10 months (all groups combined) directed their attention to faces faster than to non-face stimuli (i.e. attention capture), directed more fixations to and looked longer at faces than non-face stimuli (i.e. attention maintenance). Unimodal bilinguals demonstrated increased attention capture and attention maintenance by faces compared to monolinguals. Contrary to predictions, bimodal bilinguals did not differ from monolinguals in attention capture and maintenance by face stimuli. These results are discussed in relation to the language experience of each group and the close association between face processing and language development in social communication.